Emergency general surgery: definition and estimated burden of disease - Shafi, Shahid; Aboutanos, Michel B; Agarwal, Jr, Suresh; Brown, Carlos V R; Crandall, Marie; Feliciano, David V; Guillamondegui, Oscar; Haider, Adil; Inaba, Kenji; Osler, Turner M; Ross, Steven; Rozycki, Grace S; et al. (The journal of trauma and acute care surgery, 2013)
Acute care surgery encompasses trauma, surgical critical care, and emergency general surgery (EGS). While the first two components are well defined, the scope of EGS practice remains unclear. This article describes the work of the American Association for the Surgery of Trauma to define EGS. A total of 621 unique International Classification of Diseases-9th Rev. (ICD-9) diagnosis codes were identified using billing data (calendar year 2011) from seven large academic medical centers that practice EGS. A modified Delphi methodology was used by the American Association for the Surgery of Trauma Committee on Severity Assessment and Patient Outcomes to review these codes and achieve consensus on the definition of primary EGS diagnosis codes. National Inpatient Sample data from 2009 were used to develop a national estimate of EGS burden of disease. Several unique ICD-9 codes were identified as primary EGS diagnoses. These encompass a wide spectrum of general surgery practice, including upper and lower gastrointestinal tract, hepatobiliary and pancreatic disease, soft tissue infections, and hernias. National Inpatient Sample estimates revealed over 4 million inpatient encounters nationally in 2009 for EGS diseases. This article provides the first list of ICD-9 diagnoses codes that define the scope of EGS based on current clinical practices. These findings have wide implications for EGS workforce training, access to care, and research.